A study of geotextiles in roadway construction at Tanjung Karang – Kuala Selangor highway / Zaihasra Abdul Malik - Abdul Malik, Zaihasra (2002)
The study was conducted to determine the types of geotextile products used in the roadway construction of the Tanjung Karang - Kuala Selangor highway together with its specification. The study gathered two types from survey and interview to the project contractor, geotextiles manufacturer and the government. The project contractor was being asked about types of geotextile product used for the highway and method of installation, the geotextile manufacturer was being asked about the specification of geotextiles materials used for the highway. While the government was being asked on minimum requirement of specification of geotextiles material used in such highway construction. From the interview and survey it shows that the main manufacturer of geotextiles material used in the Tanjung Karang - Kuala Selangor highway construction is the Emaskiara Sdn. Bhd. and types of geotextiles used are the combination of geogridsgeotextiles (geocomposites) and geotextiles itself from both non woven and woven fabrics. This is because both types are applied on different position of the construction.